Validity of clinical measures of smooth pursuit eye movement control in patients with idiopathic neck pain. (February 2018) - Daly, Laura; Giffard, Phoebe; Thomas, Lucy; Treleaven, Julia
Abstract: Background: Electrooculography is useful in detecting smooth pursuit neck torsion (SPNT) abnormalities in patients with neck pain, however, a validated, clinically relevant measure is lacking. Objectives: To explore the validity of visual assessment of formal and clinical videotaped SPNT tests in comparison to electrooculography. Design: Cross-sectional observational study. Method: Twenty patients with idiopathic neck pain (INP) and twenty healthy controls performed the electrooculography SPNT test: first in neutral, then 45° trunk-under-head torsion to the left then right. The formal video test involved the participant following a horizontal laser stimulus simultaneous to electrooculography. The clinical video test was then performed where the participant followed the clinician's finger in the horizontal direction. One blinded investigator interpreted and analysed the electrooculography trace and two others interpreted the videos. Results: Patients with INP had a significantly (p < 0.05) greater SPNT difference than healthy controls. Visual observation of the formal test had 82.5% agreement with electrooculography and showed fair sensitivity (63.5%) and good specificity (89.6) whilst the clinical test had 65% agreement with electrooculography and showed poor sensitivity (27.3%) and good specificity (79.3%). There was an 82.5% agreement between investigators for the formal video taped measure. Conclusions: Visual analysis of assessment of SPNT is sufficient for detecting SPNT abnormalities in patients with INP. Accuracy of the clinical method could be improved by, altering how the visual stimulus is presented and including subjective reporting of symptoms to aid diagnosis resulting in implications for future research. Highlights: Patients with INP have deficits in SPNT. Visual observation of SPNT appears to be valid for clinical practice. Suggested modifications to the clinical test could further improve accuracy.